The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fimmu.2020.578019
|View full text |Cite
|
Sign up to set email alerts
|

Higher Cytokine and Opsonizing Antibody Production Induced by Bovine Serum Albumin (BSA)-Conjugated Tetrasaccharide Related to Streptococcus pneumoniae Type 3 Capsular Polysaccharide

Abstract: A number of studies have demonstrated the limited efficacy of S. pneumoniae type 3 capsular polysaccharide (CP) in the 13-valent pneumococcal conjugate vaccine against serotype 3 invasive pneumococcal diseases and carriage. Synthetic oligosaccharides (OSs) may provide an alternative to CPs for development of novel conjugated pneumococcal vaccines and diagnostic test systems. A comparative immunological study of di–, tri–, and tetra–bovine serum albumin (BSA) conjugates was performed. All oligosaccharides conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Antibody titers for CP in post-immunization sera were measured using ELISA. Briefly, plates coated with S. pneumoniae type 3 CP were incubated with antisera from 6 immunized mice ( 42 ). Wells were washed and secondary antibody was added, followed by incubation and washing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody titers for CP in post-immunization sera were measured using ELISA. Briefly, plates coated with S. pneumoniae type 3 CP were incubated with antisera from 6 immunized mice ( 42 ). Wells were washed and secondary antibody was added, followed by incubation and washing.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of semisynthetic glycoconjugates to stimulate cytokine production in vivo and their influence on the activation of cellular immunity remain unknown. Here, we report on the effect of a conjugate of the synthetic disaccharide, which represents a repeating unit of S. pneumoniae serotype 3 ( 42 ), on production of Th1/Th2/Th17 cytokines in mice, changes in expression of surface molecules on splenocytes, antibody response, and protection against S. pneumoniae infection. We also investigated the production of autoantibodies against double-stranded (ds) DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The Nifantiev laboratory conducted intensive research on semisynthetic pneumococcal glycoconjugate vaccines. A comparative immunological study of synthetic oligosaccharides of the CPS repeating units of ST3 [ 37 ] and ST14 [ 38 , 39 ] conjugated to bovine serum albumin (BSA) revealed that the optimal candidates for semisynthetic vaccines for both STs are tetrasaccharide ligands. Further immunological studies in mice revealed protective properties of both neoglycoconjugates.…”
Section: Antibacterial Semisynthetic Carbohydrate-based Vaccinesmentioning
confidence: 99%
“…[14][15][16][17][18][19] Therefore, several groups have focused on the synthesis of ST3 CPS oligosaccharide fragments and the discovery of immunogenic epitopes to develop ST3 oligosaccharide-based glycoconjugate vaccines. [20][21][22][23][24][25] Vliegenthart's group prepared a series of neoglycoproteins using the synthesized ST3 CPS oligosaccharides with chain lengths varying from di-to tetra-saccharide. 21 Immunological study revealed that those ST3 oligosaccharide-CRM197 conjugates could elicit robust specific IgG antibodies to provide immunoprotection against the lethal challenges of ST3.…”
Section: Introductionmentioning
confidence: 99%